The effects of perioperative intra-aortic balloon counter pulsation on left ventricular function in patients undergoing coronary artery bypass grafting - Sazzad, Md Faizus (Asian Society for Cardiovascular and Thoracic Surgery (ASCVTS), 2021)
The 25th Annual Meeting of the Asian Society for Cardiovascular and Thoracic Surgery (ASCVTS 2017)